Analytical and Numerical Solutions to the 2D Sakiadis Flow of Casson Fluid with Cross Diffusion, Inclined Magnetic Force, Viscous Dissipation and Thermal Radiation Based on Buongiorno’s Mathematical Model - Ghiasi, Emran Khoshrouye; Saleh, Reza (CFD Letters, 2021)
In this paper, the homotopy analysis method (HAM) and Runge-Kutta-Fehlberg fourthfifth order method (RKF45M) are applied to investigate the 2D Sakiadis flow of nonNewtonian Casson fluid with convective boundary conditions based on the Buongiorno’s mathematical model. The governing boundary layer equations of continuity, momentum, thermal energy and nanoparticle concentration are derived and converted to the dimensionless form via the similarity variables. The present solutions agree entirely with those available results in the literatures. A parametric study is also performed to illustrate the effects of pertinent parameters on the fluid flow. It is shown that the skin friction coefficient for a non-Newtonian fluid is found to be higher than that of the Newtonian one. Furthermore, the thermal boundary layer thickness is greatly affected by the resistive Lorentz force and viscous dissipation.